VALIDITY OF INTERACTIVE MULTIMEDIA BASED ON ADOBE FLASH IN EXCRETORY SYSTEM MATERIAL FOR SENIOR HIGH SCHOOL - Anita Juni Ersinta; Ardi Ardi; Mailizarni Mailizarni (ATRIUM PENDIDIKAN BIOLOGI, 2021)
Excretory system material is a classified as difficult to understand by studenst because the material is still abstract, all proscesses that cannot be seen directly because they are in the human body. The limitations if learning media at SMAN 8 Padang have not supported learning on ecxcretory system material. The solution to this problem is to make interactive multimedia. This study is purpose to produce learning media products in the form of interactive multimedia based on practical on excretory system material for class XI students of SMAN 8 Padang. This type of research is research and development (R&D) research with using the 4D Model. The subject of this research was two lecturer Jurusan Biology FMIPA UNP and one teacher of SMAN 8 Padang and thirty the XI grade students of SMAN 8 Padang. The result of validation shows an average value of 91,77% with a very valid category. Based on this, it can be concluded that interactive multimedia developed is valid.